Bahasa Inggris - Asti Wahyuni B; Nining Syafitri (English Education Department, 2022)
The objective of the research was to find out the level of students reading anxiety and students reading comprehension. Data collection in this research was carried out using a research instrument in the form of a questionnaire EFL Reading Anxiety Inventory (EFLRAI) consisting 23 items and test to determine the level of students reading anxiety and 30 items of reading comprehension test. The data obtained were analyzed by descriptive statistical analysis. Based on the result of the research, it was conclude that students’ reading anxiety was in the high category with the mean score 2.72 means in the high anxiety. Sequentially top-down reading anxiety with the mean score 2.77, bottom-up reading anxiety with the mean score 2.74 and classroom reading anxiety with the mean score 2.29. While reading comprehension the mean score 2.72 implies that the students’ reading comprehension is in the poor category.